Duplication and Divergence of Leucine-Rich Repeat Receptor-Like Protein Kinase (LRR-RLK) Genes in Basal Angiosperm Amborella trichopoda - Liu, Ping-Li; Xie, Lu-Lu; Li, Peng-Wei; Mao, Jian-Feng; Liu, Hui; Gao, Shu-Min; Shi, Peng-Hao; Gong, Jun-Qing (Frontiers in Plant Science, 2016)
Leucine-rich repeat receptor-like protein kinases (LRR-RLKs) are the largest group of receptor-like kinases, which are one of the largest protein superfamilies in plants, and play crucial roles in development and stress responses. Although the evolution of LRR-RLK families has been investigated in some eudicot and monocot plants, no comprehensive evolutionary studies have been performed for these genes in basal angiosperms like Amborella trichopoda. In this study, we identified 94 LRR-RLK genes in the genome of A. trichopoda. The number of LRR-RLK genes in the genome of A. trichopoda is only 17–50% of that of several eudicot and monocot species. Tandem duplication and whole-genome duplication have made limited contributions to the expansion of LRR-RLK genes in A. trichopoda. According to the phylogenetic analysis, all A. trichopoda LRR-RLK genes can be organized into 18 subfamilies, which roughly correspond to the LRR-RLK subfamilies defined in Arabidopsis thaliana. Most LRR-RLK subfamilies are characterized by highly conserved protein structures, motif compositions, and gene structures. The unique gene structure, protein structures, and protein motif compositions of each subfamily provide evidence for functional divergence among LRR-RLK subfamilies. Moreover, the expression data of LRR-RLK genes provided further evidence for the functional diversification of them. In addition, selection analyses showed that most LRR-RLK protein sites are subject to purifying selection. Our results contribute to a better understanding of the evolution of LRR-RLK gene family in angiosperm and provide a framework for further functional investigation on A. trichopoda LRR-RLKs.